Sustainable Corrosion Protection of Stainless Steel 316L in Marine Environment Using Electrophoretically Deposited Garlic Extract Green Inhibitor: Electrochemical and Surface Analysis - Arwati, IG. Ayu; Ginting, Dianta; Feriyanto, Dafit; Golwa, Gian Villany; Yuliarty, Popi; Tarigan, Kontan; Damar, Stenlly; Khuzaimah; Mashadi, Mashadi (Science and Technology Indonesia, 2026)
The increasing demand for sustainable and environmentally friendly corrosion inhibitors has driven research toward green alternatives to conventional toxic inhibitors. This study investigates the corrosion protection performance of garlic extract (Allium sativum) as an eco-friendly green inhibitor for stainless steel 316L in 3.5% NaCl marine environment. The inhibition efficiency was evaluated using electrochemical potentiodynamic polarization techniques, complemented by comprehensive surface characterization through scanning electron microscopy with energy-dispersive X-ray spectroscopy (SEM-EDX), Fourier transform infrared (FTIR) spectroscopy, Raman spectroscopy, electrochemical impedance spectroscopy (EIS), and cyclic voltammetry analysis. Electrophoretic deposition (EPD) was employed to apply garlic extract concentrations of 8, 10, and 12 mL onto SS316L specimens. Results demonstrated significant corrosion rate reduction from 0.0082732 mmpy (unprotected specimen) to 0.0014547 mmpy with 12 mL garlic extract treatment, achieving maximum inhibition efficiency of 82%. EIS revealed substantial increase in charge transfer resistance (>170 kΩ), while electrochemical analysis demonstrated mixed-type inhibition behavior with reduced corrosion current densities. SEM-EDX confirmed the formation of protective Fe2+-allicin complex layers on the metal surface, while Raman spectroscopy showed substantial reduction in corrosion products (a-Fe2O3 and y-FeOOH) formation. Cyclic voltammetry demonstrated a five-order-of-magnitude reduction in diffusion rate, confirming exceptional barrier properties. The superior performance is attributed to the chemisorption of sulfur and oxygen-containing compounds in allicin molecules onto active steel sites, forming stable protective films. This green inhibitor demonstrates excellent potential for sustainable corrosion protection in marine and industrial applications, offering an environmentally benign alternative to synthetic inhibitors.